Evolution of grain boundary network topology in 316L austenitic stainless steel during powder hot isostatic pressing. (July 2017) - Irukuvarghula, S.; Hassanin, H.; Cayron, C.; Attallah, M.M.; Stewart, D.; Preuss, M.
Abstract: The grain boundary network evolution of 316L austenitic steel powder during its densification by hot isostatic pressing (HIPing) was investigated. While the as-received powder contained a network of random high angle grain boundaries, the fully consolidated specimen had a large fraction of annealing twins, indicating that during densification, the microstructure evolves via recrystallization. By interrupting the HIPing process at different points in time, microstructural changes were tracked quantitatively at every stage using twin boundary fractions, distribution of different types of triple junctions, and the parameters associated with twin related domains (TRDs). Results revealed that, with increase in temperature, (i) the fraction of annealing twins increased steadily, but they mostly were not part of the grain boundary network in the fully consolidated specimen and (ii) the average number of grains within a TRD, the length of longest chain, and twinning polysynthetism increased during HIPing and (iii) the powder characteristics and the HIPing parameters have a strong influence on the development of grain boundary network. Based on the results obtained, possible alterations to the HIPing process are discussed, which could potentially allow twin induced grain boundary engineering. Graphical abstract: Image 1